S-27-2: RENAL WATER LOSS-INDUCED SKIN WATER CONSERVATION LEADS TO HIGH BLOOD PRESSURE IN SPONTANEOUSLY HYPERTENSIVE RATS. (January 2023) - Ogura, Takahiro; Kitada, Kento; Morisawa, Norihiko; Kidoguchi, Satoshi; Nakano, Daisuke; Titze, Jens; Nishiyama, Akira
Abstract : Objective: Although previous studies have demonstrated the pathophysiological basis of hypertension in basic and clinical sciences, the decisive mechanism of essential hypertension remains to be clarified. We recently reported that 5/6 nephrectomized rats exhibited renal water loss due to impaired renal concentration ability and that the renal water loss triggered suppression of transepidermal water loss (TEWL). This skin water conservation was achieved by skin vasoconstriction-mediated reduction in skin vascular mass, which increased blood pressure in 5/6 nephrectomized rats. In this study, we examined the effect of renal and skin water handling on high blood pressure in spontaneously hypertensive rats (SHR). Design and method: We used male 9 weeks old SHR and its control normotensive Wistar Kyoto rats (WKY) in this study. The rats were kept in metabolic cages to collect urine for 24 hours. We also collected urine under water deprivation. After the urine collection, the rats were sacrificed and their plasma and tissues were collected. Skin sodium and potassium content were measured by the ashing-flame photometer method. In a separate experiment, we compared blood pressure and TEWL in anesthetized SHR and WKY. Body temperature was raised by elevating room temperature. Results: Compared with WKY, SHR exhibited a significant increase in urine volume and a decrease in urine osmolality. There were no significant differences in plasma osmole concentrations, urinary sodium, potassium, and urea excretion between the groups. SHR showed significantly higher urine volume and lower urine osmolarity than WKY even in water deprivation, suggesting that SHR has renal water loss. SHR exhibited significantly lower TEWL and higher blood pressure and skin sodium and potassium content compared with WKY. Skin vasodilation induced by elevating body temperature significantly reduced blood pressure in SHR but not WKY. Conclusions: These findings suggest that renal water loss due to the impaired renal concentration ability induces suppression of TEWL and skin osmole accumulation in SHR. This skin water conservation leads to high blood pressure via skin vasoconstriction to reduce skin vascular mass and TEWL. Skin water conservation as a compensatory mechanism for renal water loss may be a key mechanism and novel therapeutic target for essential hypertension.